PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MATERI GAYA UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Aeni, Nita Nur; Sujana, Atep; Sunaengsih, Cucun (Jurnal Pena Ilmiah, 2017)
Findings shown that of low student learning outcomes on the material style at class 4. The action is done by applying the problem-based learning model. Problem based learning trains students in solving contextual problems. This study to determine the improvement of student learning outcomes learning . The class action research by using method of Kemmis and Mc Taggart. The technique of collecting data through observation, interviews, testÂ  and field notes. Based on data obtained shows the increase in teacher performance in the cycle IÂ  72,72%, cycle II 84,84%, and cycle III 97,97%. Student activity in cycle I 69%, cycle II 84,21%, and cycle III 94,73%. While the results of learning in the cycle I 47,36%, cycle II 78,95%, and cycle III 95%. The result show that problem based learning model can improve student learning outcomes.